Edukasi Pentingnya Skrining Pencegahan Obesitas Dikalangan Tenaga Pengajar KB-TK Atisa Dipamkara - Susy Olivia Lontoh; Novendy Novendy; Enny Irawaty; Muhammad Dzakwan Dwi Putra; Muhammad Naufal Razaan (Universitas 45 Surabaya, 2025)
Monitoring nutritional status and waist circumference is an important step in detecting potential obesity and preventing cardiometabolic complications. Educational programs about the importance of monitoring nutritional status and waist circumference are crucial for the community, especially among young adults at high risk. The FK UNTAR community service team conducted a screening program for measuring nutritional status and waist circumference. This activity aims to educate and raise awareness about the importance of monitoring nutritional status and waist circumference as an early detection method for obesity prevention. The community service activity related to nutritional status checks and waist circumference measurements was held on October 9, 2024 and attended by 23 instructors from Atisa Dipamkara. The process began with measuring weight, height, and calculating the Body Mass Index (BMI), which is the main indicator in assessing nutritional status. Most participants were an average age of 37.96 years, with the majority falling within the normal or higher nutritional status category. 69.6% of respondents were at risk of abdominal obesity, which increases the risk of metabolic diseases. The average BMI of the participants was 25.47 kg/m², indicating a tendency toward obesity. The follow-up plan for this activity includes education on healthy eating patterns, physical activity, stress management, and regular check-ups every 3-6 months to monitor health.